Social Media Scams: A Netnography Investigation in Malaysia and Indonesia - Anak Agung Gde Satia Utama; Erna Andajani; Aaiman Siddiqui; Khaslinda Akasyah Binti Mujin; Siti Rochmah Ika; Siow Xiu Yun; Parwita Setya Wardhani (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2025)
Online scams have become increasingly sophisticated across Southeast Asia, yet current studies primarily focus on single-platform fraud, specific scam types, or victim psychology in isolated contexts. Existing literature has examined romance scams, online investment fraud, digital labor scams, and general scam perceptions. However, few studies adopt a comparative Netnography approach across multiple social media platforms or explore the interconnectedness of scams with emerging issues such as human trafficking, particularly in Indonesia and Malaysia where scam incidents are rapidly escalating. This study fills this gap by providing a cross-country, multi-platform netnography investigation of scam techniques and victim responses. Using a non-participatory netnography approach, this research analyzed public interactions tagged with #scam and #scammeralert on Facebook, Instagram, and YouTube over a five-day period in 2024. The study examined scammer strategies and victim narratives drawn from scam-reporting communities and fraud-victim support groups. The findings identify four dominant scam types: (1) selling products at cheaper prices, (2) impersonation, (3) offering job with high salary, and (4) offering online part-time job. The study also reveals three major victim responses: (1) shooting and uploading the fraud on social media, (2) creating fraud’s victim association, and (3) freezing of their bank account on priority basis. This research contributes new insights by demonstrating how digital platforms function as interconnected ecosystems of fraud, where multiple scam types operate simultaneously and victims mobilize collective counteractions. The study highlights the urgent need for enhanced digital literacy, cross-border enforcement, and integrated anti-scam policies in Indonesia and Malaysia.